Tingkat Pengetahuan dan Perilaku Siswa SMA/Remaja Dalam Pencegahan Penularan Penyakit HIV/AIDS di SMA Negeri 1 Ende - Maria Elisabeth Weu; Syaputra Artama; Yustina P. M. Paschalia (Kelimutu Nursing Journal, 2026)
Background: The escalation of HIV/AIDS cases among productive age groups from global to regional levels demands serious attention, with adolescence being a highly vulnerable period due to minimal health literacy and high peer pressure. Objective: This study aims to identify the overview of knowledge levels and behavioral characteristics of adolescents in preventive efforts against HIV/AIDS transmission at SMA Negeri 1 Ende. Methods: This quantitative descriptive study utilized a cross-sectional approach. Sample selection applied a simple random sampling technique, resulting in a total of 208 eleventh-grade students as respondents. The data collection instrument employed structured questionnaires adapted from the Brief HIV Knowledge Questionnaire (HIV-KQ-18) and a preventive behavior questionnaire, which were subsequently analyzed using univariate analysis. Results: The research findings revealed that the majority of respondents possessed a low level of knowledge, accounting for 113 students (54.3%). Conversely, regarding the preventive behavior variable, most respondents demonstrated good criteria, representing 116 students (55.8%), and no students were found to be in the poor behavior category. Conclusion: There is a gap between the cognitive aspect and the practical actions of students, where limitations in deep understanding regarding HIV/AIDS do not hinder them from adopting positive preventive actions. Schools are expected to integrate specific reproductive health promotion programs to eradicate misconceptions surrounding virus transmission routes.